Preparation and Preliminary Characterization of Hybrid Alginate – Carrageenan Aerogel: Effect of Gelation Methods - M. Alnaief; B. Mohammad; Mohannad Aljarrah; R. M. Obaidat (Jordan Journal of Physics, 2025)
Aerogels are a class of nanoporous structured material with a high specific surface area, large porosity and open pore structure. Usually, they are produced by substituting the solvent of a stable gel with air without affecting the 3-D network of the gel. It is possible to engineer the produced material by controlling the precursors, gelling mechanism and drying process. In this work, hybrid aerogel based on alginate and three different types of carrageenan was produced using supercritical fluid technology. CO2- induced gelation, as well as GdL-induced gelation, were evaluated for their effect on final textural properties of the produced aerogel. CO2-induced gelation method shows enhanced aerogel properties and can be further investigated for the scale-up application. Nevertheless, GdL-induced gelation is easier to perform and produced a smaller specific surface area aerogel if compared with CO2-induced gelation method. Hybrid alginatecarrageenan aerogels were produced with high surface area (390-566) m2 ∙g -1 and large pore volume (4.2-6.8) m3 ∙g -1 and with a mesoporous structure (3.2 – 26.8) nm. The produced aerogels have great potential for future biotechnological and pharmaceutical applications. Keywords: Hybrid Aerogel, Alginate, Carrageenan, Supercritical Fluid Extraction, Drug Carrier.